NARRATIVE RECONSTRUCTION OF TRAUMATIC MEMORY IN THE NOVEL OF REDEMPTION AT HACKSAW RIDGE - Neisya, Neisya; Aprilia, Fitria; Rahmah, Anisa Syafiah (English Review: Journal of English Education, 2023)
This research discusses the traumatic memory of Desmond Doss and analyzes Herndon’s narrative reconstruction of Desmond’s traumatic memory in his novel. This research uses the post-memory theory by Hirsch, through Freytag’s pyramid approach. The qualitative method and literary memory are use in this research. Data were acquired from the documentary interview, and the paragraphs that existed on every page of the novel. The researchers collected the date through four steps: exploration, reduction, abstraction, and read intensively. This research reveals that Desmond Doss experienced seven traumatic memories; he was frightened of the gun, intimidated, humiliated, lost his friend, Japanese Army strategies, and the aftermath. To make it entertaining to read, Herndon caught Desmond’s traumatic memory and reconstructed the narratives into his novel. To fulfill Herndon's and the reader’s satisfaction, he exaggerates and lessens some of the actual events. The purpose of narrative reconstruction in this novel was to modify what the author could not do in the past and fix it in the novel through his imaginative investment, along with highlighting the heroic story of Desmond Doss.